(untitled) (Eurasian Research Bulletin, 2022)
The ability to interpret the text, as many researchers rightly point out, allows you to join the author’s vision of the world, enrich yourself spiritually, improve a person’s spiritual culture. When analyzing a literary text, lexical and stylistic means are usually given the dominant place, but syntactic means, which have come to the fore in modern literature, play an important role in creating the expressiveness of the text, in understanding the main idea of the work and the author’s worldview. But it should be noted that the problem of punctuation in general linguistics is still waiting for its solution: there is no single definition of the term "punctuation", there are disputes about the functions performed by it, the question of the leading principle of punctuation has not been resolved.